PERAN HAKIM AD HOC PERIKANAN PADA PENGADILAN NEGERI MERAUKE DALAM MENYUSUN PUTUSAN - Tanggoi, Simon Petrus (Animha Law Journal, 2024)
The aim of this research is to determine the existence of ad hoc fisheries judges in the criminal justice system in Indonesia and the role of ad hoc judges in directly handling fisheries crimes at the Merauke District Court. This research uses an empirical juridical method which uses statutory regulations as a benchmark and looks at facts and phenomena in the field. The results of this research show that the existence of ad hoc fisheries judges is based on the need to have special knowledge and expertise in the field of fisheries to be able to decide complex and technical cases. The existence of ad hoc fisheries judges can be a relevant alternative in the Indonesian justice system for handling cases in the fisheries sector. Then the role of ad hoc fisheries judges in handling fisheries crimes is to decide fisheries crime cases, apply appropriate penalties, considering technical and scientific aspects, upholding justice and legal principles, and educating the public about fisheries law, so that since its formation the role of ad hoc judges has been appropriate in carrying out their duties as stated in the fisheries law. Another thing is that in the panel's deliberations as per Article 197 of the Criminal Procedure Code letter (g), the ad hoc judge provided many technical facts about adaptation in the fisheries sector. In this way, the role of ad hoc judges can be ensured to be capable and experienced in the field of fisheries and can provide a sense of justice with appropriate decisions and contribute to effective fisheries law enforcement.